Dampak Objek Wisata Religi Makam Sultan Suriansyah Terhadap Pelaku Usaha Sekitar kawasan Kajian Aspek Ekonomi dan Pendidikan - Rofiati, Rofiati; Rahmini, Noor (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This research aims to (1) describe the profiles of business actors in relation to the presence of the religious tourism site, Sultan Suriansyah's Tomb, (2) elucidate the economic impacts of Sultan Suriansyah's Tomb as a religious tourism site, and (3) examine its educational impacts. The study involved 14 respondents, comprising business community members residing around the tourism site. It employed a quantitative descriptive research method, utilizing interviews with questionnaires, observations, and documentation as data collection techniques. The findings indicate an increase in income before and after businesses began operating at the religious tourism site. However, in terms of business opportunities and employment absorption, the impact remains limited. Conversely, regarding education, the presence of Sultan Suriansyah's Tomb has positively affected the ability of business actors to provide adequate education to their children.